The Role of Syzygium Polyanthum Leaf Extract in Reducing Renal Cell Damage with Potassium Oxonate-Induced Hyperuricemia - Dwimantoro; Hotimah Masdan Salim; Aditya Bhayusakti; Dayu Satriya Wibawa (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2022)
Abstract. Background: Kidney is an organ that plays an important rolein regulating homeostasis, excrete the foreign or toxic substances, andmetabolism product such as uric acid, urea, and creatinine in the bodythrough the urine. Syzygium polyanthum, has been used in loweringuric acid levels. The purpose of this research is to tested the effect ofbay leaf extract on kidney histopathology of hyperuricemia inducedmice model of potassium oxonate. Methods: This study is a laboratoryexperimentalstudy with a post-test only control group design, and wasdivided into a control group, a hyperuricemia (PO) group, an PO groupwith 75 mg/kg bay leaf extract, an PO group with 150 bay leaf extractand an PO group with 300 mg/kgBW bay leaf extract. The treatmentwas given for 14 days then histopathological examination of thekidneys was carried out with HE staining. Results: Histopathologicalinflammation occurred in all groups and necrosis was the most severefound in the positive control group where the administration of bayleaf extractsignificantly reduced inflammatory cellsfrom the lowest tothe highest dose with P < 0.001. Conclusion: Administration ofSyzygium polyanthum affected renal histopathology in potassiumoxonate-induced hyperuricemic mice.